Pemberdayaan Masyarakat Pesisir Kampung Dela dalam Meningkatkan Ketangguhan terhadap Bencana Alam melalui Mitigasi dan Infrastruktur Evakuasi - Rusdi, Achmad; Febriadi, Ihsan; Purnawati, Renny; Arifin , Herlina; Ibal, La; Kewila, Ameli Moni; Alitiong, M. Wahyudi; Nahsim Yenusi, Rohelio Velri; Sagisolo, Moses Alfando; Maukary, Kalvin M.; Ode, Muh. Arif; Ferdinandus, Ferdinandus; Kambu, Sintia Putry (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2025)
The Della Village Coastal Community Empowerment Program aims to increase community resilience to natural disasters through mitigation activities and evacuation infrastructure development. Implementation methods include initial survey, needs mapping, evacuation route construction, disaster mitigation training, evacuation simulations, and monitoring and evaluation. Activities were carried out participatively, involving the community, village government, and university students. Pretest results showed community knowledge on disaster mitigation was low, ranging from 25% to 40%. After training and simulation, posttest results increased significantly to 70–80%, showing improved understanding and preparedness. Beyond increasing knowledge, the activity encouraged collective awareness, social responsibility, and practical skills in dealing with emergencies. The evacuation infrastructure strengthened the village's physical readiness for potential earthquakes and tsunamis. The program proved the effectiveness of educational and participatory approaches in building disaster-resilient communities in remote coastal areas. Overall, the activity helped strengthen adaptive capacity and sustainability of community-based mitigation in Della Village